2018
DOI: 10.4236/ojapps.2018.812046
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Oral Hygiene Practices among Medical Practitioners in Delta State, Nigeria

Abstract: Background: The knowledge of good oral hygiene is of paramount importance for the technical knowhow to keep one's mouth clean and free from periodontal diseases. Thus, one's attitude towards oral hygiene directly affects the oral health status. Aims: The study aimed at evaluating the knowledge, attitude and oral hygiene practices among medical practitioners in Delta State, Nigeria. The research also aimed at determining the effect of sex on knowledge, attitude and oral hygiene practices. Methodology: This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…In terms of the practice of oral hygiene, the current study revealed that a significant majority of the respondents, specifically 130 (55.8%) respondents, demonstrated a commendable level of oral hygiene practices. In comparison, this finding aligns with prior studies conducted in Nepal, India and Nigeria [30][31][32][33], suggesting a consistent trend of positive oral hygiene behaviours among participants across these diverse regions. The convergence of results emphasizes the universal significance of oral health awareness and education in fostering good oral care habits on a global scale.On the contrary, the current study contradicts the findings from research conducted in Malaysia, Saudi Arabia and southern Ethiopia [21,28,34], which reported poor oral hygiene practices among their respondents.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the practice of oral hygiene, the current study revealed that a significant majority of the respondents, specifically 130 (55.8%) respondents, demonstrated a commendable level of oral hygiene practices. In comparison, this finding aligns with prior studies conducted in Nepal, India and Nigeria [30][31][32][33], suggesting a consistent trend of positive oral hygiene behaviours among participants across these diverse regions. The convergence of results emphasizes the universal significance of oral health awareness and education in fostering good oral care habits on a global scale.On the contrary, the current study contradicts the findings from research conducted in Malaysia, Saudi Arabia and southern Ethiopia [21,28,34], which reported poor oral hygiene practices among their respondents.…”
Section: Discussionsupporting
confidence: 90%